2018
DOI: 10.1002/pssa.201700658
|View full text |Cite
|
Sign up to set email alerts
|

A Hydrogen Plasma Treatment for Soft and Selective Silicon Nitride Etching

Abstract: In this paper, the development of a soft and selective method to increase the etching rate and control accurately the etched thickness of Si3N4 material is reported. This technique combines the low damage characteristics of wet etching with the anisotropy of plasma etching which is compatible with the requirements of many surface sensitive electronic devices such as MOS transistors. This consists on a local modification of the Si3N4 layer using hydrogen‐based plasma followed by wet chemical etching in buffered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
(43 reference statements)
2
7
0
Order By: Relevance
“…The less intense peak at 1530 cm –1 is ascribed to −NH 2 groups. These results are in agreement with data reported by Bouchilaoun, who observed increases in the intensities of peaks related to Si–H and N–H bonds using ex situ transmittance FTIR. Our results confirm that the concentration of N–H bonds initially increased and then plateaued at ∼15 s, while the Si–H bond concentration also increased over time but stabilized after 60 s. Additionally, as the hydrogen exposure time was increased, the bands related to −NH x groups and Si–H bonds shifted toward lower wavenumbers.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The less intense peak at 1530 cm –1 is ascribed to −NH 2 groups. These results are in agreement with data reported by Bouchilaoun, who observed increases in the intensities of peaks related to Si–H and N–H bonds using ex situ transmittance FTIR. Our results confirm that the concentration of N–H bonds initially increased and then plateaued at ∼15 s, while the Si–H bond concentration also increased over time but stabilized after 60 s. Additionally, as the hydrogen exposure time was increased, the bands related to −NH x groups and Si–H bonds shifted toward lower wavenumbers.…”
Section: Resultssupporting
confidence: 93%
“…This indicates that the Si–N bond can be substituted to the N–H bond by hydrogen ions. Thus, chemical changes such as the production of N–H and Si–H bonds can increase the hydrogen content in SiN films subjected to a hydrogen plasma …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 22 ] Hydrogen ion was found to exhibit a higher reactivity with nitrogen than Si to form N–H bonds or outfluxes in the SiN films. [ 18,21,48 ] The hydrogen and its surface reaction caused the ER decrease at a lower temperature for the PE‐SiN films because of the formation of N–H x layer (around 400 eV) on the surface of the samples, as confirmed by Figure 9a,b, the N 1s XPS spectra with a TOA of 15° (more surface sensitive) for T s = 20°C and –20°C. On the contrary, for the LP‐SiN films, we learned that the T s only had a minor effect on ER because the films exhibited the almost identical surface structure regardless of T s , as shown in Figure 9c,d, the N 1s spectra with a TOA of 20°.…”
Section: Discussionmentioning
confidence: 77%
“…The influences of hydrogen content in the SiN films on their wet etching behaviors have been investigated. [ 18,19 ] In dry process etching, the comparative studies on the etching behaviors of the PE‐ and LP‐SiN have been investigated by CF 4 /H 2 and CF 4 /O 2 plasmas. [ 12,20 ] It has been shown that the etch behavior of the two kinds of SiN was very similar by using CF 4 /H 2 plasma with different hydrogen additions.…”
Section: Introductionmentioning
confidence: 99%